An improved particle method for simulating Fluid-Structure Interactions: The multi-resolution SPH-VCPM approach. (1st March 2022) - Ng, K.C.; Alexiadis, A.; Ng, Y.L.
Abstract: In this paper, the computational efficiency of our previous Smoothed Particle Hydrodynamics-Volume Compensated Particle Method (SPH-VCPM) is enhanced by incorporating a multi-resolution strategy for solving Fluid-Structure Interaction (FSI) problems involving free surface. Different spatial and temporal resolutions are used in solid and fluid bodies. In order to match the velocity marching interval during the time integrations of momentum equations for fluid and solid bodies, the position-based Verlet time integration scheme is implemented. The force coupling between SPH and VCPM is established by treating the VCPM solid particles near the fluid-solid interface as dummy particles for SPH. The convergence and stability of the multi-resolution SPH-VCPM method is firstly tested by using two quasi-static benchmark cases, i.e. hydrostatic water column on an Aluminum plate and cantilever beam subjected to gravity and buoyancy in a quiescent fluid. For the hydrostatic test case, the speed-up is ∼11x when different time and spatial resolutions are applied while not affecting the solution accuracy significantly. The solver is then used to solve a variety of dynamic FSI problems involving dam-breaking and sloshing. The results are verified against the benchmark solutions and the agreements are encouraging. Highlights: 1. A multi-resolution particle method for solving FSI problems with free surface. 2. Different spatial and temporal resolutions are used for solid and fluid bodies. 3. Significant speedup is obtained while maintaining the solution accuracy. 4. The coupling procedure at the solid-liquid interface is highlighted.